PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM PENINGKATAN MUTU PENDIDIKAN DI SDN 55 MATTIROWALIE KECAMATAN MANIANGPAJO KABUPATEN WAJO - Andi Irmawanti; Muhammad Arafah; Tenri Sau (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the management of the School Operational Assistance Fund (BOS) in improving the quality of education at SDN 55 Mattirowalie and to identify the factors that support and hinder its management. This study employs a qualitative approach using a descriptive research design. Data were collected through interviews, observations, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the management of BOS funds at SDN 55 Mattirowalie is carried out through three stages: the planning stage, where the school develops the Annual School Budget Plan (RKAS) in a participatory manner involving the principal, treasurer, teachers, and the school committee; the implementation stage, where the use of BOS funds is carried out in accordance with the RKAS and applicable technical guidelines; These funds are used to support learning activities, maintenance of facilities and infrastructure, and other school activities. In the accountability stage, the school prepares a report on fund usage in an orderly manner through the ARKAS application and shares information with the school committee and the community as a form of transparency. Supporting factors for BOS fund management include the commitment of the management team, cooperation among school stakeholders, and support from the school committee and parents. In addition, the availability of administrative tools and coordination with the education office also contribute to the smooth operation of the program. However, there are several challenges, including limited funding due to the small number of students, limited internet access, and the heavy workload of the treasurer, who also serves as a classroom teacher.